A Source of Bias in Public Opinion Stability - DRUCKMAN, JAMES N.; FEIN, JORDAN; LEEPER, THOMAS J. (The American political science review, 2012)
A long acknowledged but seldom addressed problem with political communication experiments concerns the use of captive participants. Study participants rarely have the opportunity to choose information themselves, instead receiving whatever information the experimenter provides. We relax this assumption in the context of an over-time framing experiment focused on opinions about health care policy. Our results dramatically deviate from extant understandings of over-time communication effects. Allowing individuals to choose information themselves—a common situation on many political issues—leads to the preeminence of early frames and the rejection of later frames. Instead of opinion decay, we find dogmatic adherence to opinions formed in response to the first frame to which participants were exposed (i.e., staunch opinion stability). The effects match those that occur when early frames are repeated multiple times. The results suggest that opinion stability may often reflect biased information seeking. Moreover, the findings have implications for a range of topics including the micro–macro disconnect in studies of public opinion, political polarization, normative evaluations of public opinion, the role of inequality considerations in the debate about health care, and, perhaps most importantly, the design of experimental studies of public opinion.